Rheology of rounded mammalian cells over continuous high-frequencies - Gotthold Fläschner (Nature Portfolio, 2021)
While rheology studies have contributed to the understanding of the viscoelastic properties of living cells, the use of higher frequencies promises elucidate the link between cellular and molecular properties. Here authors introduce a rheological assay that measures the cell mechanical response across a continuous frequency range ≈ 1 – 40 kHz.